The Use of Think Bingo Game to Improve Students’ Vocabulary Mastery - Rita Noviyanti; Syamsul Bahri; Chairina Nasir (Research in English and Education Journal, 2019)
Vocabulary is one of the keys to learn a language especially English because knowing sufficient vocabulary will affect the four skills that must be mastered by the students. A good teacher must know strategies to improve the students' vocabulary and one of the them is Bingo game.  The aim of this research was to find out whether the use of Bingo game can improve students’ vocabulary at SMPN 16 Banda Aceh or not.  In this research, the researcher took 20 students from VIII-3 class as the sample. The research design of this research was one group pretest and posttest design.  To collect the data, the researcher used a vocabulary test which containing 20 questions on pretest and posttest. The calculation result of this research shows that the tscore = 6,18 ttable = 1.72 with the level significance 0.05 and the degree of freedom (df) 19. Therefore, (Ho) is rejected and (Ha) is accepted. In line with this, it can be concluded that Bingo game can improve students’ vocabulary mastery and Bingo game can be recommended as one of the great strategies in teaching vocabulary to students.